2017
DOI: 10.1108/ijhcqa-07-2016-0104
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to support and develop clinician-researcher leadership in one health district

Abstract: Purpose Clinical leadership, researcher capacity and a culture of clinical inquiry are needed in the clinical workforce. The purpose of this paper is to report on a program which was used to develop and support clinicians to explore practice, implement innovation, translate evidence and build researcher capacity. Design/methodology/approach This pragmatic paper presents a case study of a nursing and midwifery clinician-researcher development program. The multi-site, multi-modal program focused on education, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…No authors indicated if the clinical leadership programmes were informed by theory, with some developed based on identified gaps in staff leadership capabilities. For example, Fry and Dombkins, 11 Williams et al 12 and Debono et al 10 co-designed their programmes informed by interviews and consultations with key stakeholders within the hospital setting, while Clarke et al 13 developed their leadership programme based on consultation with consumers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No authors indicated if the clinical leadership programmes were informed by theory, with some developed based on identified gaps in staff leadership capabilities. For example, Fry and Dombkins, 11 Williams et al 12 and Debono et al 10 co-designed their programmes informed by interviews and consultations with key stakeholders within the hospital setting, while Clarke et al 13 developed their leadership programme based on consultation with consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Clarke et al 13 developed the 'Take the Lead' Programme (TTL), which supported NUM to be more competent leaders in their role through five leadership enhancement modules. In terms of duration, the four programmes ranged from 38 weeks 12 to 3 years, 11 offering leadership development in a long-term capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are examples of such roles in the United States leading to financial reward during and post completion of internships and post-graduate study [36], the lack of financial support for internships was seen as a fundamental barrier internationally [17,18,33,36]. Additionally, the lack of time release (for both Interns and mentors) and impingement on the work-life balance was often cited as a major conflict [9,18,33,36,38]. With these potential opportunities and barriers in mind, the evaluation study aimed to explore stakeholder perceptions of the benefits and challenges of the HEE/NIHR Research Internship model, alongside reviewing intern research career progression within and beyond the Internship.…”
Section: Introductionmentioning
confidence: 99%
“…Building a base for translating redesign knowledge into clinical practice is stronger with input from academics, who generally have a better knowledge of tools such as ethics processes, publication avenues and external funding opportunities than clinical staff. Having academic involvement in these aspects assists in building a research culture and developing research networks within the clinical practice environment [32]. Furthermore, publication and other dissemination activities, such as conference presentations, reports and sharing positive results via social media, are also ways to celebrate achievement and develop the positive culture required for the longevity and sustainability of the redesign [33].…”
Section: Introductionmentioning
confidence: 99%